Challenges and solutions for a rational vaccine design for TB-endemic regions. (August 2015) - Gowthaman, Uthaman; Mushtaq, Khurram; Tan, Amabel C.; Rai, Pradeep K.; Jackson, David C.; Agrewala, Javed N.
Abstract Vaccines have been successful for global eradication or control of dreaded diseases such as smallpox, diphtheria, tetanus, yellow fever, whooping cough, polio, and measles. Unfortunately, this success has not been achieved for controlling tuberculosis (TB) worldwide. Bacillus Calmette Guérin (BCG) is the only available vaccine against TB. Paradoxically, BCG has deciphered success in the Western world but has failed in TB-endemic areas. In this article, we highlight and discuss the aspects of immunity responsible for controlling Mycobacterium tuberculosis infection and factors responsible for the failure of BCG in TB-endemic countries. In addition, we also suggest strategies that contribute toward the development of successful vaccine in protecting populations where BCG has failed.